2020
DOI: 10.2174/2666255813666190912114043
|View full text |Cite
|
Sign up to set email alerts
|

Medical Device Rules - 2017, India: An Insight

Abstract: According to “Medical Device Rules-2017” (MDR-2017), “Medical Devices (MDs) are the substances which are used for in-vitro diagnosis and surgical dressings, surgical bandages, surgical staples, surgical sutures, ligatures, blood, and blood component collection bag with or without anticoagulant and substances including mechanical contraceptives, disinfectants and insecticides and devices notified from time to time under sub-clause (iv) of clause (b) of section 3 of the Drugs and Cosmetics Act, 1940”. According … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Classification and regulation of surgical devices is controlled by the Health Ministry of India (part of the Indian Government) [36] , [37] . The manufacturer’s regulatory team identified that the RAIS system is considered as a Class-A device (Low-risk surgical instrument) and worked with the Design Team to compile the requisite documentation.…”
Section: Resultsmentioning
confidence: 99%
“…Classification and regulation of surgical devices is controlled by the Health Ministry of India (part of the Indian Government) [36] , [37] . The manufacturer’s regulatory team identified that the RAIS system is considered as a Class-A device (Low-risk surgical instrument) and worked with the Design Team to compile the requisite documentation.…”
Section: Resultsmentioning
confidence: 99%
“…Class II & III devices, as well as Class I devices having a measuring or sterility function, that must provide evidence of compliance with the relevant EU Directives & the particular mentioned throughout the conformity review process. Other Class I medical devices are not subject to pre-market compliances, but must adhere to mandatory safety & effectiveness principles in their design, manufacture, & labeling requirements [16].…”
Section: Overview Of European Medicines Agency (Ema)mentioning
confidence: 99%